2010
DOI: 10.1038/jid.2009.211
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase-Mediated, Context-Dependent Function of Amphiregulin and HB-EGF in Human Keratinocytes and Skin

Abstract: Human keratinocytes (KCs) express multiple EGF receptor (EGFR) ligands; however, their functions in specific cellular contexts remain largely undefined. To address this issue, first we measured mRNA and protein levels for multiple EGFR ligands in KCs and skin. Amphiregulin (AREG) was by far the most abundant EGFR ligand in cultured KCs, with > 19 times more mRNA and > 7.5 times more shed protein than any other family member. EGFR ligand expression in normal skin was low (< 8 ‰ of RPLP0/36B4); however, HB-EGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
63
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 68 publications
12
63
0
Order By: Relevance
“…In line with recent findings (Stoll et al, 2010a), our data showed that AREG is the most highly transcribed EGFR ligand in normal (control) N-TERT keratinocytes (about 70% of GAPDH expression level). TGFa message was detected at the level of about 10% of GAPDH while other EGFR ligands showed no or negligible expression in control cells (Fig.…”
Section: Depletion Of Arnt Results In Downregulation Of Amphiregulin supporting
confidence: 79%
See 1 more Smart Citation
“…In line with recent findings (Stoll et al, 2010a), our data showed that AREG is the most highly transcribed EGFR ligand in normal (control) N-TERT keratinocytes (about 70% of GAPDH expression level). TGFa message was detected at the level of about 10% of GAPDH while other EGFR ligands showed no or negligible expression in control cells (Fig.…”
Section: Depletion Of Arnt Results In Downregulation Of Amphiregulin supporting
confidence: 79%
“…In line with previous reports designating AREG as a principal EGFR ligand mediating autocrine growth in epidermal keratinocytes (Piepkorn et al, 1994;Nylander et al, 1998;Stoll et al, 2010a) we showed that AREG is the most abundant EGFR ligand in normal N-TERT cells. In N-KO keratinocytes AREG declined significantly at both mRNA and protein levels and its nuclear positivity was completely lost (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Amphiregulin and HB-EGF show different biological activities in target cells (21), with amphiregulin mainly stimulating cell proliferation (22) and HB-EGF stimulating chemotaxis (23). Amphiregulin binds to ErbB1 (EGFR), whereas HB-EGF binds to both ErbB1 (EGFR) and ErbB4 (24).…”
Section: Hb-egf Markedly Enhances Migration and Proliferation Of Humamentioning
confidence: 99%
“…In this study, we focused on one target of miR-132 -HB-EGF -which is one of the EGFR ligands, in addition to TGFα, amphiregulin (AR), epiregulin (EREG), and β cellulin, that is expressed by keratinocytes in an autocrine fashion (39,40). Unlike the other EGFs, overexpression of HB-EGF in keratinocytes was previously reported to lead to a large decrease in cell Inhibition of miR-132 delays reepithelialization of human ex vivo skin wounds.…”
Section: Lack Of Mir-132 Delays Skin Wound Healing In Vivomentioning
confidence: 99%